Evaluasi Strategi WASH dalam Menurunkan Kejadian Diare pada Balita: Tinjauan Literature terhadap Pencapaian Tujuan SDG’s 2030 - Syafana Afra Febriyana; Triana Srisantyorini; Suherman Jaksa (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This literature review evaluates the effectiveness of Water, Sanitation, and Hygiene (WASH) strategies in reducing the prevalence of diarrhea among children under five, with the aim of assessing their contribution to achieving the 2030 Sustainable Development Goals (SDGs). The study employed a systematic literature review of publications indexed in Scopus, PubMed, ScienceDirect, and Google Scholar, focusing on articles published between 2016 and 2026. The search was conducted using the keywords “WASH,” “diarrhea,” “2030 Sustainable Development Goals (SDGs),” “hygiene,” and “sanitation.” The review highlights the significant impact of hygiene practices and environmental sanitation on the incidence of diarrheal disease. The findings indicate that handwashing with soap, access to safe drinking water, adequate sanitation facilities, and effective waste management are essential components of diarrhea prevention. Evidence consistently demonstrates a significant association between improved sanitation and hygiene practices and a reduction in diarrheal cases among children under five. Furthermore, the review emphasizes the importance of health education and community-based interventions in promoting sustainable WASH practices. However, the implementation of WASH interventions continues to face challenges, including socioeconomic disparities, inadequate infrastructure, and limited community participation. This review concludes that comprehensive WASH strategies, integrating infrastructure improvements with behavior change interventions, are critical for achieving the health-, clean water-, and sanitation-related targets of the 2030 Sustainable Development Goals and for reducing the burden of diarrhea among children under five.